Asuhan Keperawatan Gerontik Pada Pasien Asam Urat (Gout Arthritis) Dengan Pemberian Intervensi Spiritual Emotional Freedom Technique (Seft) Terhadap Kualitas Tidur Di Panti Werdha Kasih Ayah Bunda Tangerang 2023 - Dede Nurjanah; Siti Robeatul Adawiyah; Rina Puspita Sari; Siti Rahayu (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Background: The results of a survey by the United Nation International Children Found (UNICEF, 2019), the most common diseases in the elderly are non-communicable diseases, including hypertension, joint disease, diabetes mellitus, heart disease, stroke, and Gout Arthritis. This can happen considering that the elderly have a declining body work system and there are still many poor lifestyles, eating patterns, and sleep patterns in the elderly, sleep pattern disturbances are a problem that often occurs in the elderly. There are two ways to treat sleep disorders, namely pharmacological and non-pharmacological. Non-pharmacological can be done with SEFT (Spiritual Emotional Freedom Technique) complementary therapy to improve sleep quality. Purpose: the purpose of this paper is to provide an overview of nursing care for Gout Arthritis patients who experience sleep pattern disturbances with the SEFT intervention on sleep quality. Method: case study design using nursing care. The case study sample used 1 patient. Results: based on the implementation results on Tn.S with the application of SEFT therapy for 7 days, data were obtained on the first day of the PSQI scale, namely 23 (≥5, meaning poor sleep quality), then on day 7 it dropped to a PSQI score of 14 (moderate sleep quality). it can be concluded that with changes towards improvement, this indicates the effect of SEFT (Spiritual Emotional Freedom Technique) therapy on sleep quality in elderly patients with Gout Arthritis.